Semi-perfect colourings of hyperbolic tilings - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2011)
If G is the symmetry group of an uncoloured tiling, then a colouring of the tiling is semi-perfect if the associated colour group is a subgroup of G of index 2. Results are presented that show how to identify and construct semi-perfect colourings of symmetrical tilings. Semi-perfectly coloured tilings that emerge from the hyperbolic semi-regular tiling 8·10·16 are reported.